The Ecological Competence of Future Specialists - A V Gagarin; A V Ivaschenko (Peoples' Friendship University of Russia (RUDN University), 2014)
The study aims at identifying the essence-functional and structure- and content-related particularities of future employees' environmental competence, as well as the conditions and factors of its development. It features the results of the theoretical and empirical analysis of the issue and outlines the prospects for future research.